Dignified Teacher Working Conditions in the 21st Century, an Inalienable Right, not an Option - Guiselle María Garbanzo-Vargas (Universidad Nacional, Costa Rica, 2011)
The author develops the topic of appropriate teacher working conditions in the challenging 21st Century. The objective is the contextualization of the emergent society in the 21st Century; propose a review of the Latin American educational context and the working conditions of education professionals. Another objective is to review the working conditions of teachers in different educations systems, including Europe and Latin America, among others. The profile of the 21st Century educator is defined in this paper, in comparison to teachers in the traditional society. In addition, this paper includes some indicators of consensus in different educational realities, and their integration in the cognitive, operational and institutional areas. The main conclusions include the necessity of policy-making to support dignified teacher working conditions, which is basic for an inclusive education of quality, in accordance with the demands of a challenging emerging society. The author concludes that this issue does not come to an end; it must always be in the educational agenda of society.